Enhanced anti-wear property of VCN coating in seawater with the optimization of bias voltage. Issue 6 (15th April 2020) - Ye, Yuwei; Jiang, Zilong; Zou, Yangjun; Guo, Shengda; Zeng, Xianhui; Yi, Zhou; Yu, Jiangwei; Gui, Jiabin; Liu, Tingguang; Chen, Hao
Abstract: Through multi-arc ion plating technology, the VCN coatings were successfully prepared under various bias voltages. The microstructure, mechanical property, anti-corrosion capability and tribological performance of these VCN coatings were comparatively studied. With the bias voltage increased from −25 to −100 V, the adhesion force and hardness of VCN coatings increased by 73.33% (22.5 to 39 N) and 14.83% (31.7 to 36.4 GPa). Besides, the toughness, corrosion resistance and anti-wear ability of VCN coatings were enhanced to varying degrees by changing the bias voltage. By contrast, the VCN coating at −100 V presented the smallest friction coefficient (COF) of 0.113 and wear rate of 5.25 × 10 −7 mm 3 /Nm, implying an attractive protective effect for key friction parts in marine environment.